2019
DOI: 10.1111/1759-7714.13096
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside inhibits migration and invasion of poorly differentiated thyroid cancer cells

Abstract: Background No effective treatment is currently available for poorly differentiated thyroid cancer which is resistant to radioiodine, especially with migration and invasion. A great number of researches have revealed the anticancer effects of salidroside, but none have studied the effects of salidroside on thyroid cancer. This study aimed to investigate the effect of salidroside on migration and invasion of poorly differentiated thyroid cancer cells. Methods The effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…In normal cells, salidroside plays important roles in anti-inflammation, anti-stress, antioxidant, anti-aging, and anti-viral activities [ 46 ], while in cancer cells, salidroside inhibits cell proliferation and induces cell apoptosis, including urinary bladder cancer, breast cancer, gastric and colorectal cancer, lung cancer, nasopharyngeal carcinoma (NPC), and sarcoma [ 46 , 47 ]. Meanwhile, salidroside had no cytotoxic effect on the normal cells, such as thyroid follicular epithelial cells and human mammary epithelial cells, when it inhibited the cellular migration and invasion in poorly differentiated thyroid cancer cells or breast cancer cells with the drug concentrations of 5~40 µM [ 48 , 49 ]. Furthermore, salidroside could inhibit the growth of NPC xenografts, transplanted solid Ehrlich adenocarcinoma, and Pliss lymphosarcoma [ 47 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In normal cells, salidroside plays important roles in anti-inflammation, anti-stress, antioxidant, anti-aging, and anti-viral activities [ 46 ], while in cancer cells, salidroside inhibits cell proliferation and induces cell apoptosis, including urinary bladder cancer, breast cancer, gastric and colorectal cancer, lung cancer, nasopharyngeal carcinoma (NPC), and sarcoma [ 46 , 47 ]. Meanwhile, salidroside had no cytotoxic effect on the normal cells, such as thyroid follicular epithelial cells and human mammary epithelial cells, when it inhibited the cellular migration and invasion in poorly differentiated thyroid cancer cells or breast cancer cells with the drug concentrations of 5~40 µM [ 48 , 49 ]. Furthermore, salidroside could inhibit the growth of NPC xenografts, transplanted solid Ehrlich adenocarcinoma, and Pliss lymphosarcoma [ 47 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell migration and invasion are important factors in tumor metastasis that are associated with the prognosis for patients with thyroid cancer ( 25 , 26 ). The ANGPTL1 mRNA levels were compared between DTC patients with N0 (no lymphatic metastasis) and N1 (lymph node metastasis) stage using TCGA data.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, other studies have reported conflicting results. In thyroid cancer WRO cells, Sal significantly restrained cell migration and invasion, and induced apoptosis by activating JAK2/STAT3 pathway and promoting cleaved caspase-3 level [ 48 ]. These findings suggest that Sal could regulate Akt/NF-κB and Caspase-3/GSDME pathways, but the activation or inactivation might differ in different diseases.…”
Section: Discussionmentioning
confidence: 99%